PENGUATAN NILAI-NILAI ISLAM PADA PESERTA DIDIK MELALUI PROGRAM PESANTREN INTENSIF STUDI DI SEKOLAH MENENGAH KEJURUAN PLUS ALMAARIF SINGOSARI - MALANG - Faisal Ghufron Hasan; Mohammad Afifulloh; Kukuh o Santos (Vicratina : Jurnal Ilmiah Keagamaan, 2022)
The current of modernization is growing and has a huge impact on students. Thenegative impact of modernization must be anticipated properly throughstrengthening Islamic values in students. Therefore, the researcher wants to discussstrengthening Islamic values in students through an intensive study program at SMKPlus Al-Maarif Singosari. The research method used is descriptive qualitative researchusing 3 data collection procedures (observation, interview, and documentation). Theresults of this study indicate that the main background of the intensive pesantrenprogram is to fortify students from the influence of modernization. In addition, theplanning for strengthening Islamic values in this program is through the halaqahdiniyah program, guidance on basic books and intensive boarding schools. Theimplementation is by recitation of the Al-Quran using the sorogan method andrecitation of the yellow book using the lecture, discussion, question and answer methodand imlak.